MENINGKATKAN HASIL BELAJAR IPA MELALUI MODEL PEMBELAJARAN NUMBERED HEADS TOGETHER PADA SISWA KELAS V SD NEGERI DAYA I KECAMATAN BIRINGKANAYA KOTA MAKASSAR - Ince Prabu Setiawan Bakar (ALGAZALI INTERNATIONAL JOURNAL EDUCATIONAL RESEARCH, 2020)
Abstract: Improving Science Learning Outcomes through the Numbered Heads Together Learning Model in the Class V Students of SD Negeri Daya I Biringkanaya Makassar. This research was a Classroom Action Research that aimd to improve the learning outcomes of Natural Sciences through the Numbered Heads Together learning model in fifth grade students of SD Negeri I Biringkanaya Makassar. This type of classroom action research was divided into two cycles with four stages: planning, action, observation, and reflection. The data analysis technique was qualitative, while the data in the form of numbers or quantitative data were analyzed by calculating the percentage of students understanding of natural science subjects in fifth grade students of SD Negeri Daya 1 Biringkanaya Makassar, on the material properties of light due to the teacher creating varied learning conditions. The application of Numbered Heads Together learning model was used as an alternative in the material about the properties of light. This study aimed to improve learning outcomes on the material properties of light. An increase in the quality of learning was characterized by an increase in the average activity of students in the learning process in accordance with the results of observation during class action, where the average score of the end result of the first cycle was 64.33, an increase of 86.66 in the second cycle. Likewise with mastery learning from the first cycle 43.33% increased by 90% in the second cycle.              Keywords: Numbered Heads Together learning model, Natural Science Learning Outcome